Argumentation in religious education in England: an analysis of locally agreed syllabuses. Issue 4 (2nd October 2021) - Chan, Jessica; Fancourt, Nigel; Guilfoyle, Liam
ABSTRACT: The importance of developing students' ability to argue effectively is generally recognised across the curriculum, however what this means within religious education has not been thoroughly investigated. We explore this issue first through an initial review of both wider philosophical and curriculum literature on argumentation, notably Toulmin's work, and then a review of relevant research within religious education. We then describe our curriculum analysis, addressing three research questions focusing on the frequency, purpose and conceptualisation of argumentation, though a mixed-methods curriculum analysis of locally agreed syllabuses across England (LASs). A quantitative analysis of frequency in thirty-five LASs showed that although argumentation was never mentioned, other cognates were always present. A detailed qualitative analysis of six LASs showed that its purpose was linked to personal expression within democratic participation, and epistemic and empathetic flexibility. Using Toulmin's model of argumentation as a frame, it is generally conceptualised around the elements of claim, evidence and rebuttal, but the precise nature of evidence, warrant and backing are not explicit, especially as the field-dependent elements are unspecified. The implications of these findings for both general conceptualisations of argumentation and curriculum development within religious education are outlined.